Іконостас монастирської церкви села Сокілець на Тернопільщині - Чуйко, О. (Інститут народознавства НАН України, 2007)
In the article the author analyzes the insufficiently known iconostasis of Our Lady Pokrova Cloister in the village of Sokilets’, Buchach district, Ternopil’ oblast’. The iconographic image program comprises basic principles of subject and thematic selection of icon-painting images which have close analogies to the iconostasises of cloisters circle of Galicia. At the same time it is complemented with subjects and themes, which were important for a particular functioning church, environment and burning questions of the church ideology.